Forest continuity acts congruently with stand maturity in structuring the functional composition of saproxylic beetles. (January 2017) - Janssen, Philippe; Fuhr, Marc; Cateau, Eugénie; Nusillard, Benoit; Bouget, Christophe
Abstract: Long temporal continuity in forests has been shown to influence biodiversity through dispersal and recruitment limitations. However, for motile taxa that depend on stand maturity attributes, these limitations may be less relevant. Moreover, while certain habitats may be created rapidly, the development of other habitats may take a long time. Forest continuity and stand maturity may therefore have additive effects on biodiversity. Understanding their relative influence on biodiversity is crucial for conservation. We explored the response of species and functional trait composition of saproxylic beetle assemblages using a balanced sampling design in which we crossed forest continuity (ancient vs recent) and stand maturity (mature vs overmature). We established forty plots in montane forests where we sampled beetles. Stand maturity, related to deadwood resources, induced a strong environmental filtering on both species and functional trait composition. Regardless of forest continuity, species preferring large wood of late decay stages were more abundant in overmature stands. Moreover, overmature stands enhanced the co-occurrence of different saproxylic beetles with contrasting resource requirements. Forest continuity interacting with stand maturity induced taxonomic and functional changes in communities. Compared to other forest types, overmature stands in ancient forests hosted assemblages with many more characteristic species, with a larger average body size and species that prefer large deadwood pieces. Finally, a greater diversity of body sizes was found in these forests. Saproxylic species conservation should therefore benefit from strategies that favor setting-aside overmature stands in ancient forests, promoting sites with higher amounts and heterogeneity of deadwood. Highlights: Stand maturity rather than forest continuity shaped assemblage structures. Forest continuity interacts with stand maturity in providing valuable habitats. Ancient-overmature stands hosted species preferring large decayed deadwood. Large-bodied species were more abundant in ancient-overmature stands. Conservation policies should chiefly focus on overmature stands in ancient forests.